ANTIMICROBIAL STEWARDSHIP ACROSS THE SURGICAL PATHWAY - Sartelli, Massimo; Detanac, Dzemail (Sanamed, 2025)
Antimicrobial stewardship programs (ASPs) help ensure antibiotics are used effectively to treat infections, reduce side effects, and slow the spread of antibiotic resistance. Improving collaboration among healthcare professionals is the most important way to strengthen ASPs in hospitals. So far, most ASPs have focused on medical specialities and applied the same approach to all hospital settings. In surgery, it is essential to understand the local cultural and contextual factors that shape prescribing habits so targeted strategies can be developed. Antibiotic stewardship in surgery must be integrated with strict infection prevention and source control, as all three work together to improve patient care. Effective ASPs usually combine persuasive strategies, which educate and influence prescribers, with restrictive ones, which limit certain practices. While clinical guidelines turn evidence into practice and improve the quality of care, they do not always fit local realities. Adapting them into locally relevant tools, such as protocols, bundles, checklists, and posters, can boost acceptance and adherence. Actively involving prescribers in developing these tools increases the likelihood of meaningful change. Clearly defining responsibilities for specific actions within these protocols helps ensure they are followed.